The geographic distribution of Costa Rican velvet worms (Onychophora: Peripatidae) - Barquero González, José Pablo (2016)
Velvet worms, “peripatus” or onychophorans, are “living fossils” that were geographically widespread in Cambrian seas but now occur exclusively on terrestrial habitats. The only extant species studied in some detail are those from Costa Rica, but their real geographic distribution was in urgent need of revision. To solve this problem we visited the localities mentioned in all the original taxonomic descriptions and redescriptions. These visits covered a 25 year period (1988-2014) and included interviews with local residents. We also examined all Costa Rican collections, and checked the information in old maps and books. Here we critically review geographic data, correct errors, assign neotype localities, report on the survival of populations after heavy volcanic eruptions or urbanization, and present the correct geographical distribution for the seven currently described Costa Rican species.